Environmental Refugees: A Case Study Of Haitian Immigration To Brazil (2010-2018) - Lima Bezerra de Souza, Larissa (Journal of Scientific Initiation on International Relations, 2021)
The following work will deal with the theme of environmental refuge, which is understood, even if not legally, as the immigration flows that were initially motivated by an environmental disaster. A case study will be carried out on Haitian immigration to Brazil, between 2010 and 2018, based on the question whether these immigrants can be considered environmental refugees, based on the hypothesis that the 2010 earthquake and Hurricane Matthew, in 2016, commented on the reasons that triggered the Haitian immigration flow to Brazil. The general objective of the work is to identify a Haitian motivation for immigration to Brazil. For this, the hypothetical-deductive method will be used, with an explanatory and descriptive research. The results achieved partially corroborate with a hypothesis. Between 2010 and 2013 there is a direct correspondence between the proposed guidelines for the identification of environmental refugees and Haitian immigration to Brazil. However, there is a complexity as of 2014, manifesting other primary elements for the arrival of these immigrants, which would not make them environmental refugees.